1973
DOI: 10.1144/sjg09010063
|View full text |Cite
|
Sign up to set email alerts
|

The structure and structural dating of the Carn Chuinneag intrusion, Ross-shire

Abstract: Synopsis The Carn Chuinneag intrusion is a foliated granite pluton emplaced in the Moine rocks of the Northern Highlands of Scotland, containing large irregular inclusions of amphibolite. Minor sheet-like apophyses at the margin of the pluton extend into the Moine country rocks. The emplacement occurred after D 1 in static conditions and the Moinian envelope was distended. Structure contours suggest that the intrusion was originally a sheet-like pluton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…It is the dominant tectonic fabric in the area, but it appears to have been depicted as D l in figure 4b of Shepherd (1973). It is consistent in style and orientation with that associated with the Sgurr Beag slide zone.…”
Section: Cam Chuinneagmentioning
confidence: 82%
See 3 more Smart Citations
“…It is the dominant tectonic fabric in the area, but it appears to have been depicted as D l in figure 4b of Shepherd (1973). It is consistent in style and orientation with that associated with the Sgurr Beag slide zone.…”
Section: Cam Chuinneagmentioning
confidence: 82%
“…Rb-Sr whole-rock and bulk fraction zircon studies suggested an emplacement age of about 560 Ma, subsequently supported by four near-concordant U-Pb SHRIMP zircon ages in the range 540-620 Ma (Pidgeon and Compston 1992). Shepherd (1973) interpreted the intrusions as emplaced post-Dl, pre-D2 in the structural sequence, the inference being that Dl is Proterozoic. The dominant structure is D2 which consists of folds with a congruous L-S fabric that affects both the country rocks and intrusions, strongly rodding and foliating the latter.…”
Section: Cam Chuinneagmentioning
confidence: 99%
See 2 more Smart Citations
“…Three successive sets of tectonic structures occur within the Morar Group in the Achness Thrust Sheet (see also Shepherd 1973, Kelley & Powell 1985. S2 Ac is the dominant fabric, characterised by preferred orientation of biotite, muscovite and quartz ribbons.…”
Section: Detailed Structurementioning
confidence: 99%